2021
DOI: 10.1111/apt.16549
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review with meta‐analysis: dietary intake in adults with inflammatory bowel disease

Abstract: Summary Background Poor dietary intake is associated with the development of malnutrition, micronutrient deficiencies, anaemia and osteoporosis in individuals with inflammatory bowel disease. While trials are underway to manipulate the diet of people with IBD, there has been no comprehensive systematic review of the dietary intake of adults with IBD. Aims To conduct a systematic evaluation and meta‐analysis of the dietary intake of adults with IBD, including macronutrients, micronutrients and food group data. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 77 publications
1
22
0
2
Order By: Relevance
“…Generally, L-serine is contained in proteinrich foods, such as meat, fish, eggs, and soybeans. A recent systematic review has shown that fiber and calcium intakes are insufficient in IBD, whereas protein intake meets or exceeds the recommended amount (Lambert et al, 2021). Therefore, the reduced concentration of L-serine in the gut lumen of individuals with IBD may be caused by the excessive consumption of L-serine by the gut microbiota or the host cells rather than by the insufficient intake of protein.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, L-serine is contained in proteinrich foods, such as meat, fish, eggs, and soybeans. A recent systematic review has shown that fiber and calcium intakes are insufficient in IBD, whereas protein intake meets or exceeds the recommended amount (Lambert et al, 2021). Therefore, the reduced concentration of L-serine in the gut lumen of individuals with IBD may be caused by the excessive consumption of L-serine by the gut microbiota or the host cells rather than by the insufficient intake of protein.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, L-serine is contained in protein-rich foods, such as meat, fish, eggs, and soybeans. A recent systematic review has shown that fiber and calcium intakes are insufficient in IBD, whereas protein intake meets or exceeds the recommended amount (Lambert et al, 2021). Therefore, the reduced concentration of L-serine in the gut lumen of individuals with IBD may be caused by the excessive consumption of L-serine by the gut microbiota or the host cells rather than by the insufficient intake of protein.…”
Section: Discussionmentioning
confidence: 99%
“…Недавно проведенный метаанализ 19-ти исследований продемонстрировал важную роль питания в развитии ВЗК [8]. Целью этого исследования стало обобщение данных о повседневном рационе питания взрослых с ВЗК по сравнению со здоровыми людьми, сопоставимыми по возрасту и полу.…”
Section: факторы риска развития и прогрессирования якunclassified